Inflammatory Signatures of Tinnitus in Patients and Mice - Shuai Cheng; Qi Zhao; Guiyuan Rong; Shichu Sun; Hongjie Wang; Zhiyong Tan; Yonghua Ji; You Zhou (Neuroscience Bulletin, 2026)

Remediation effects of humic acid and hydroxyapatite on cadmium-contaminated alkaline wheat soil and its microbial community response: A field trial - Yineng Lu; Haoyu Yue; Rong Tan; Zihao Ding; Geng Chen; Shuangting Zhang; Ziyi Li; Ram Proshad; Xiuwen Cheng; Zhuanjun Zhao (Journal of Environmental Sciences, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Mechanisms of failure and permeability evolution in gas-bearing strata under tunnel-induced stress paths - Jiafeng Tan; Deyi Jiang; Rong Liu; Yi He; Jinyang Fan; Jianyu Liang; Cheng Qian; Hanlin He; Hong Zheng (Transportation Geotechnics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Goethite-humic acid composites for multi-metal soil remediation: Mechanisms and environmental transformation - Xiangbang Ma; Ram Proshad; Yineng Lu; Rong Tan; Zihao Ding; Geng Cheng; Ziyi Li; Shuangting Zhang; Zhuanjun Zhao (Journal of Environmental Chemical Engineering, 2025)

Enhancing soil quality and maize growth while reducing Cd accumulation with biochar and humic acid in northwestern China - Ziyi Li; Xiangbang Ma; Shuangting Zhang; Geng Chen; Yineng Lu; Rong Tan; Ram Proshad; Xifeng Zhang; Xiuwen Cheng; Zhuanjun Zhao (Journal of Environmental Chemical Engineering, 2025)

Global techno-economic analysis of MBR for hospital wastewater treatment - Junqing He; Zhenxing Zhang; Fangnan Cui; Xue Tan; Xiang Zheng; Rong Cheng (Science of The Total Environment, 2024)

Enhanced tetracycline degradation by manganic iron‑manganese compounds with peroxymonosulfate(PMS): Experimental optimization and environmental fate estimation - Ruixi Ni; Jiale Tan; Rong Tan; Yineng Lu; Jiangwei Shang; Xiuwen Cheng (Journal of Water Process Engineering, 2024)

Photocorrosion suppression of copper sulfide via hybridization with amino-functionalized metal–organic framework for natural sunlight-driven photocatalysis - Zewei Liu; Cheng Tang; Zepeng Yu; Shu Li; Chengzhang Deng; Sijie Liu; Zhiqiang Wu; Rong Tan (Fuel, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Litter traps: A comparison of four marine habitats as sinks for anthropogenic marine macro-litter in Singapore - Jenny Fong; Samuel Hsien Rong Lee; Yuchen Sun; Cheng Ling Lim; Yean Ai Jolin Tan; Yi Hong Tan; Mei Lin Neo (Marine Pollution Bulletin, 2023)

Enantioselective effect of the chiral fungicide tebuconazole on the microbiota community and antibiotic resistance genes in the soil and earthworm gut - Chao-Feng Li; Yi-Rong Zhang; Zhen-Chao Tan; Hui-Juan Xu; Cheng-Lan Liu (Science of The Total Environment, 2023)

Molecular identification of a flavone synthase I/flavanone 3β-hydroxylase bifunctional enzyme from fern species Psilotum nudum - Jie Fu; Piao-Yi Wang; Rong Ni; Jiao-Zhen Zhang; Ting-Ting Zhu; Hui Tan; Jing Zhang; Hong-Xiang Lou; Ai-Xia Cheng (Plant Science, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Numerical simulations of incompressible fluid flow in synthetic fractures using lattice Boltzmann method - Guan Rong; Long Cheng; Junsong Quan; Yaosheng Tan; Renhui He; Jie Tan (Arabian Journal of Geosciences, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

A Forchheimer Equation-Based Flow Model for Fluid Flow Through Rock Fracture During Shear - Guan Rong; Jie Yang; Long Cheng; Jie Tan; Jun Peng; Chuangbing Zhou (Rock Mechanics and Rock Engineering, 2018)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Longikaurin E induces apoptosis of pancreatic cancer cells via modulation of the p38 and PI3K/AKT pathways by ROS - Hai-bo Cheng; Yun Bo; Wei-xing Shen; Xian-guo Ren; Jia-ni Tan; Zhi-rong Jia; Chang-Liang Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Effect of a single-dose rifampin on the pharmacokinetics of pitavastatin in healthy volunteers - Yao Chen; Wei Zhang; Wei-hua Huang; Zhi-rong Tan; Yi-cheng Wang; Xi Huang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)